The Correlation between Educational Levels, Fields of Study, and Program Types and the Ability to Work in a Team - Mészáros, Ádám; Csiszárik-Kocsir, Ágnes (Journal of Ecohumanism, 2024)
The 21st century has rewritten the map of competences. New concepts such as agility, teamwork, project approach and many more have emerged. "Team player" is a typical buzzword in CVs, a term we use to describe ourselves based on our own perceptions. However, team spirit can be influenced by many factors during our studies, not only on the practical side, but also by the nature of the training module. The project approach, and in particular teamwork in the agile methodology, is of particular importance, so its learning and development can be important already during the studies. In our study, we undertake to map out some of the background factors of teamwork as a mystique, based on the results of a primary quantitative study, using statistical methods and correlation quizzes as a function of educational levels and training characteristics.